Zaramillidae, a new amphipod family from the subantarctic Kerguelen Islands (Amphipoda, Senticaudata, Gammaroidea, Zaramillidae fam. nov.) - Lowry, J.k.; Myers, A.a (Zootaxa, 2016)
A new senticaudate amphipod family, Zaramillidae is described from the subantarctic Kerguelen Islands, based on the genus Zaramilla Stebbing, 1888. It is placed in the gammaridiran amphipods.